Effects of isoquinoline alkaloids as an alternative to antibiotic on oxidative stress, inflammatory status, and cecal microbiome of broilers under high stocking density - Kittisak Insawake; Thaweesak Songserm; Ornprapun Songserm; Atthawoot Plaiboon; Nitipong Homwong; Kazeem D. Adeyemi; Konkawat Rassmidatta; Yuwares Ruangpanit (Poultry Science)
This study investigated the effect of isoquinoline alkaloids as an alternative to bacitracin on growth performance, oxidative stress, inflammatory status, and ceca microbiome of broilers raised under high stocking density (HSD). A total of 1,500 one-day-old male Ross 308 chicks were randomly assigned to five treatment groups, with 10 replicate pens per group and 30 birds per pen, for 37 days. The treatments included normal stocking density (NSD, 10 birds/m²), HSD (15 birds/m²), HSD with 50 ppm Bacitracin (BCT50), HSD with 80 ppm isoquinoline alkaloids (IQA80), and HSD with 100 ppm isoquinoline alkaloids (IQA100). From days 11 to 24, HSD birds had lower feed efficiency (P < 0.05) compared to those in other treatments. The heterophil-to-lymphocyte ratio and malondialdehyde levels were lower in NSD and IQA80 birds compared to HSD and BCT50 birds (P < 0.05). HSD birds had higher IL-6 and a lower villus height and villus height-to-crypt depth ratio compared to birds in other groups (P < 0.05). Serum TNF-α was lower in NSD and IQA80 birds compared to those in the HSD group. Alpha diversity was not affected by the treatments; however, beta diversity was lower in HSD birds compared to other treatments. HSD birds showed reduced microbial diversity, with a higher prevalence of Enterococcaceae and Peptostreptococcaceae. NSD enhanced the abundance of Lactobacillaceae, Clostridiaceae, and Rikenellaceae. BCT50 increased and decreased the abundance of Enterococcaceae and Rikenellaceae respectively. IQA80 and IQA100 increased the abundance of Lachnospiraceae, Leuconostocaceae, and Coriobacteriaceae. HSD altered metabolic pathways related to carbohydrate and lipid metabolism, and amino acid biosynthesis. BCT50 modulated microbial functions, particularly those related to cell wall synthesis, while isoquinoline alkaloids upregulated pathways involved in energy production, secondary metabolite biosynthesis, and antioxidant production. Both Bacitracin and isoquinoline alkaloids were effective in mitigating the negative effects of HSD on immunity, gut health and microbiota in broilers. Given the concerns about antimicrobial resistance, isoquinoline alkaloids are a potent alternative to bacitracin, with IQA80 being particularly recommended.